ANALISIS DAYA SAING PARIWISATA KABUPATEN SUMBAWA UNTUK MENINGKATKAN EKONOMI DAERAH - Binar Dwiyanto Pamungkas; Rosiana Sesanti (Pusat Riset dan Publikasi, 2023)
This study aims to analyze the measure of competitiveness and to analyze the competitiveness factors of the tourism industry in Sumbawa District. The type of this study was descriptive quantitative study. The methods used to collect data in this study were documentation and literature study. The data used in this study was secondary data. The data analysis tools used in this study were the tourism index, composite index, tourism competitiveness index and contribution analysis in which consist of contribution formula and contribution analysis scale. The results of the study showed that the tourism competitiveness of the eight indicators of variable infrastructure development indicator (IDI), the Environment Indicator determiner (EI), Human Resources Indicator (HRI), Social Development Indicator (SDI) showed high competitiveness value while the other eight indicators showed low value of competitiveness. The results of the analysis of the contribution of the tourism sector to the Local Revenue of Sumbawa Regency in 2017-2022 are in the very less category. The percentage contribution of the tourism sector to the PAD of Sumbawa Regency over the past six years has been below 10% (<10%).